(untitled) (Eurasian Journal of Ecology, 2016)
Thin structure of rats’ lung at various diets and physical activity is investigated in the work. Cellular and subcellular structurally and functional mechanisms of reactivity of respiratory bed of the lung white rats on influence of various food allowances and physical activity are revealed. Compensatory and adaptation reactions of cells of the alveolar bed lungs completely are remained at the maintenance of animals on a low-calorie diet when the body weight of skilled animals had decreased on the average by 20%. The high-calorific diet aggravated destructive changes of mitochondrions with fragmentation and lizisy the krist, especially it was observed in the alveolotsits of the I-st type. These data explain results of research in which violation of acid-base balance in the organism, being characterized by the excess content of milk acid, forming surplus not until the end oxidized of carbohydrate and fatty exchange products is shown. As a result of it the respiratory acidosis connected with insufficient allocation from the organism of carbonic acid legkimiya is shown.